Readings : ethics in public office - Sto. Tomas, Patricia A. (Philippines : Fiscal Administration Foundation, 1989)
Reviews on the state of ethical practices in our public service too often end with the lame excuse blaming the last war for our deteriorated and still deteriorating standards.
Part I. By way of Preface- A vision of the uncorrupted society -- Part II. Congress and the public trust -- Part III. Code of conduct and ethical standards for public officials and employees of the Republic of the Philippines.
Keywords: ETHICS